POTENTIAL EVALUAION OF EARLY MIOCENE SHALE GAS FORMATION AT KUTAI BASIN EAST KALIMANTAN - Hamdani, Ahmad
Unconventional shale gas hydrocarbon has been developed for many decade, although non-conventional shale gas reservoirs have long been studied in all parts of the world, these conditions are still relatively new in Indonesia, the research just entering the investigation or preliminary stages. Based on the history of exploration, the Kutai Basin has proven to be a productive basin and has great potential, this fact indicating the existing petroleum system has been running well. Therefore, more specific investigations need to be carried out, especially for development of non-conventional hydrocarbon reserves, It aims to find out in detail the characteristics of rocks that have the potential to be carriers of potential shale gas in the Kutai Basin. The data used in this study included 5 (five) drilling wells, namely Ramin-1, Rasamala-1, Buat-1, Busang-1, and Murung-1 which contained wireline log data, mud logs, biostratigraphic analysis, geochemical analysis, and 81line 2-D seismik trajectories. Further interpretation using geochemical data and modelling with Passey Method, produces a total value of organic carbon each depth. In geomechanical data analysis, modeling used wireline logs, produce Young modulus values, Poisson ratios, and rock brittleness. Petrophysical analysis used to be a parameter of rock quality. These data are depicted vertically and horizontally with seismik data benchmark, resulting in facies distribution and rock quality parameters as shale gas reservoirs. The research showed that the Early Miocene Rock which consist of Pulobalang and Pamaluan Formation in the study area, deposited in the deltaic to slope environment, with type III kerogen, TOC content level poor until excelent with 0.12 - 7% value and brittleness value 0.05-0.971. The calculation was conducted based standar criteria as shale gas reservoir, total potential of shale gas resources in the Pamaluan Formation 25.37 TCF while in the Pulobalang Formation the total potential of shale gas reaches 2.78 TCF.